Obstructive Sleep Apnea and Dyslipidemia: Implications for Atherosclerosis - Drager, Luciano F. (2010)
PURPOSE OF REVIEW: The aim of this review is to summarize current evidence about the impact of Obstructive Sleep Apnea (OSA) and Intermittent Hypoxia (IH) on dyslipidemia and provide future perspectives in this area. RECENT FINDINGS: IH, a hallmark of OSA, induces hyperlipidemia in lean mice. Hyperlipidemia of IH occurs, at least in part, due to activation of the transcription factor sterol regulatory element–binding protein-1 (SREBP-1) and an important downstream enzyme of triglyceride and phospholipid biosynthesis, stearoyl-coenzyme A desaturase-1 (SCD-1). Furthermore, IH may regulate SREBP-1 and SCD-1 via the transcription factor hypoxia-inducible factor 1. In contrast, key genes involved in cholesterol biosynthesis, SREBP-2 and 3-hydroxy-3-methylglutaryl-CoA (HMG-CoA) reductase, are unaffected by IH. In humans, there is no definitive evidence regarding the effect of OSA on dyslipidemia. Several cross-sectional studies suggest that OSA is independently associated with increased levels of total cholesterol, LDL and triglycerides, whereas others report no such relationship. Some non-randomized and randomized studies show that OSA treatment with continuous positive airway pressure may have a beneficial effect on lipid profile. SUMMARY: There is increasing evidence that IH is independently associated with dyslipidemia. However, the role of OSA in causality of dyslipidemia remains to be established.